2021
DOI: 10.1016/j.sjbs.2021.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic acid improved diabetes mellitus-induced testicular damage and sperm abnormalities by activation of Nrf2

Abstract: Diabetes mellitus induces testicular damage, increases sperm abnormalities, and impairs reproductive dysfunction due to induction of endocrine disturbance and testicular oxidative stress. This study evaluated the reproductive protective effect of ellagic acid (EA) against testicular damage and abnormalities in sperm parameters in Streptozotocin (STZ)-induced diabetic rats (T1DM) and examined some possible mechanisms of protection. Adult male rats were segregated into 5 groups (n = 12 rat/each) as control, cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 68 publications
0
1
0
Order By: Relevance
“…In addition, the data of this study also confirmed inflammation in the LVs of these rats by the significant upregulation in the mRNA levels and nuclear levels of NF-κB and higher levels of ICAM-1, TNF-α, IL-6, and IL-1β. These data follow many other studies that have also shown similar results on the reduction in these antioxidant levels and in the elevation of MDA, TNF-α, IL-6, and collagen levels, as well as the of NF-κB in the hearts of STZ-diabetic rats [32,[50][51][52][53][54][55][56][57]. However, restoring all of these biochemical endpoints in the LVs of these rats was our strongest evidence that the cardioprotective effect of ESA is mediated by suppressing oxidative stress, inflammation, and fibrosis.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In addition, the data of this study also confirmed inflammation in the LVs of these rats by the significant upregulation in the mRNA levels and nuclear levels of NF-κB and higher levels of ICAM-1, TNF-α, IL-6, and IL-1β. These data follow many other studies that have also shown similar results on the reduction in these antioxidant levels and in the elevation of MDA, TNF-α, IL-6, and collagen levels, as well as the of NF-κB in the hearts of STZ-diabetic rats [32,[50][51][52][53][54][55][56][57]. However, restoring all of these biochemical endpoints in the LVs of these rats was our strongest evidence that the cardioprotective effect of ESA is mediated by suppressing oxidative stress, inflammation, and fibrosis.…”
Section: Discussionsupporting
confidence: 91%
“…The utilized dose of ESA showed hypoglycemic and hypolipidemic effects in mice and rats [28,31]. We previously tested and used brusatol to suppress Nrf2 activities in vivo in rats [32]. Treatment with ESA was administered orally via a gavage feeding needle daily.…”
Section: Experimental Groupsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both StAR and CYP11A1 play critical roles in testicular development and spermatogenesis by regulating androgen production and are the rate-limiting factors of steroidogenesis ( 42 ), while SOCS3 is related to androgen production and sperm production in rats ( 43 ). Research has shown that diets supplemented with fruit pulp ( 44 ) or ellagic acid ( 45 ) improve reproductive function in male rats by increasing the circulatory levels of testosterone and up-regulating steroidogenic gene expression. Furthermore, dietary fibre intake up-regulated the expression of AMH and AMHR2 .…”
Section: Discussionmentioning
confidence: 99%